Bacterial invasion and persistence: critical events in the pathogenesis of periodontitis?. (8th December 2014) - Ji, S.; Choi, Y. S.; Choi, Y.
<x xml:space="preserve">Abstract</x> Periodontitis is chronic inflammation of the periodontium caused by the host's inflammatory response to plaque biofilm, which destroys tooth‐supporting soft and hard tissues. Periodontitis is a complex disease that involves interactions among three main features – microbial challenge, the host immune response, and environmental and genetic risk factors – in its pathogenesis. Although periodontitis has been regarded as the result of hyperimmune or hyperinflammatory responses to plaque bacteria, recent studies indicate that periodontal pathogens are rather poor activators and/or suppressors of the host immune response. This raises the question of how periodontal pathogens cause inflammation. To resolve this issue, in the present review we propose that bacterial invasion into gingival tissue is a key event in the initiation of periodontitis and that the persistence of these bacteria within host tissue results in chronic inflammation. In support of this hypothesis, we present the ways in which microbial, environmental and genetic risk factors contribute to bacterial invasion. It is hoped that the current model will instigate active discussion and new research to complete the puzzle of this complex disease process.